Outside in - Underwood, Deborah (Houghton Mifflin Harcourt, 2020)
From the New York Times best-selling author behind The Quiet Book comes a mindful contemplation on the many ways nature affects our everyday lives, even when we're stuck inside. Five starred reviews! Perfect for fans of Joyce Sidman and Julie Fogliano, Outside In reminds emerging readers of the ways nature creates and touches our lives in homes, apartments, and cars, and is the perfect homeschooling tool to reflect on the world's connectedness. Outside is waiting, the most patient playmate of all. The most generous friend. The most miraculous inventor. This thought-provoking picture book poetically underscores our powerful and enduring connection with nature, not so easily obscured by lives spent indoors. Rhythmic, powerful language shows us how our world is made and the many ways Outside comes in to help and heal us, and reminds us that we are all part of a much greater universe. Emotive illustrations evoke the beauty, simplicity, and wonder that await us all ... outside. - Publisher.